1996
DOI: 10.1007/bf00189547
|View full text |Cite
|
Sign up to set email alerts
|

Controlled multicenter trial of laparoscopic transabdominal preperitoneal hernioplasty vs Shouldice herniorrhaphy

Abstract: Laparoscopic hernia repair causes less pain than the conventional operation and enables the patient to return to full work and usual activities earlier. The recurrence rate will not be known for 5 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 2 publications
1
6
0
4
Order By: Relevance
“…21,22 In this study we found a similar trend with fewer patients complaining of chronic pain at 6 months, as compared with the numbers at the 6 th month of follow up. We found that in Group 'A' the incidence of pain at rest had decreased from 6 at one month to 0 at six months that of pain on coughing 5 times had decreased from 10 to 0 respectively at 1 and 6 months.…”
Section: Clinical Testing At 6 Monthssupporting
confidence: 79%
“…21,22 In this study we found a similar trend with fewer patients complaining of chronic pain at 6 months, as compared with the numbers at the 6 th month of follow up. We found that in Group 'A' the incidence of pain at rest had decreased from 6 at one month to 0 at six months that of pain on coughing 5 times had decreased from 10 to 0 respectively at 1 and 6 months.…”
Section: Clinical Testing At 6 Monthssupporting
confidence: 79%
“…Negative randomized controlled trials [2,12,15,17], suggesting that the laparoscopic technique offers little gain, have been offset by many positive randomized controlled trials [8,10,11,13,14,[18][19][20][21][22][23]. However, faster return to work, touted as the salient advantage of the laparoscopic repair by its proponents, was not supported by data in six trials [2,8,12,15,17,19].…”
mentioning
confidence: 89%
“…When fixation below the iliopubic tract is avoided, the incidence of nerve injury dramatically improves [37]. Controlled studies now demonstrate an advantage for the laparoscopic repair [30,39]. A more recent study by Rosenberger et al [32], however, has demonstrated that in 15-25% of patients the posterior nerves are aberrantly located above the iliopubic tract, placing them at risk even when the fixation is properly placed.…”
Section: How Far Have We Come?mentioning
confidence: 97%